What really are the best 100m performances? - Mureika, J. R. (arXiv e-print repository, 1997)
A quick and fun investigation into the effects of correcting for wind assistance/resistance and drag on 100m sprint performances. Considered are World 100m rankings, as well as Canadian rankings